STUDI MINAT GEN Z DALAM BERUSAHATANI KARET DI DESA DURIAN DAUN KECAMATAN SUAK TAPEH KABUPATEN BANYUASIN - Amalia, Riska; Kurniawan, Rahmat (Universitas Muhammadiyah Palembang, 2024)
ABSTRACTThis research aims to determine the characteristics of Gen Z in rubber farming and to determine the factors that influence Gen Z's interest in rubber farming. This research was carried out in Durian Daun Village, Suak Tapeh District, Banyuasin Regency. The research method used was the survey method. The technique. Random sampling is sampling at random. The data collection methods used in this research were observation, interviews and documentation. Data processing methods were data editing, coding, tabulation. The results of this research are the characteristics of Gen Z who are engaged in rubber farming in Durian Daun Village, Suak Tapeh District, Banyuasin Regency, namely Gen Z, aged 17-27, gender is mostly male, highest education is S1, has a land area of 0.9 ha – 1.5 ha. Income of IDR 1,680,000 – IDR 4,000,000, Farming experience from 5-10 years, has 1-3 dependents, Gen Z job is rubber farmer, employee. Factors that influence Gen Z's interest in rubber farming in Durian Daun Village, Suak Tapeh District, Banyuasin Regency, namely Gen Z's interest from internal factors in terms of education, gets an interest value of 19.08 which is categorized as high, Land area has an interest value of 15.6 which is categorized as medium, income, an interest value of 16.3 is categorized as medium, judging from external factors in terms of the family environment, an interest value of 17.04 is categorized as high, agricultural image, an interest value of 15.3 is categorized as medium, social status, an interest value of 13.6 is categorized as medium. ABSTRAKPenelitian ini bertujuan untuk mengetahui karakteristik gen z berusahatani karet dan untuk mengetahui faktor yang mempengaruhi minat gen z berusahatani karet. Penelitian ini dilaksanakan di Desa Durian Daun Kecamatan Suak Tapeh Kabupaten Banyuasin.Metode penelitian yang digunakan metode survey Teknik. Random sampling adalah pengambilan sampling secara random..Metode pengumpulan data yang digunakan dalam penelitian ini adalah pengamatan,wawancara,dan dokumentasi.Metode pengelolahan data adalah pengeditan data,pengkodean,tabulasi.Hasil penelitian ini adalah Karakteristik gen z yang berusahatani karet di Desa Durian Daun Kecamatan Suak tapeh kab Banyuasin yaitu Gen z umur dari 17-27,jenis kelamin lebih banyak laki-laki,Pendidikan tertinggi S1,memiliki luas lahan dari 0,9 ha – 1,5 ha.Pendapatan sebesar Rp1.680.000 – Rp 4.000.000,Pengalaman berusahatani dari 5-10 tahun,memiliki jumlah tanggungan 1-3,pekerjaan gen z yaitu petani karet, karyawan.Faktor-faktor yang mempengaruhi minat gen z berusahatani karet di Desa Durian Daun Kecamatan Suak tapeh kab Banyuasin yaitu minat gen z dari faktor internal sisi pendidikan mendapatkan nilai minat 19,08 yang kategorikan tinggi,Luas lahan nilai minat 15,6 dikategorikan sedang,pendapatan nilai minat 16,3 dikategorikan sedang,dilihat dari faktor eksternal dari sisi lingkungan keluarga nilai minat 17,04 dikategorikan tinggi,image pertanian nilai minat 15,3 dikategorikan sedang,status sosial nilai minat 13,6 dikategorikan sedang.